Poly(lactic acid) nanofibers containing phosphorylcholine grafts for transdermal drug delivery systems - OKTAY, BURCU; DEMİR, SERAP; KAYAMAN APOHAN, NİLHAN (My University, 2022)
The continuous and prolonged releases of chemotherapeutic drugs are required for successful treatment in cancer treatment. The project focused on a new material design to meet this requirement. We developed a constant and sustained release system and investigated the release profiles of Paclitaxel (PTX). Polylactic acid (PLA) nanofiber surface was grafted with poly (methacryloyloxyethyl phosphorylcholine) (PMPC) by the UV-induced grafting method. The morphological structure of the PLA nanofibers did not change with an increase in the MPC content. PMPC blocks contribute to the solubility of PTX, which shows low resolution. When the amount of MPC is 5%, the PTX loading efficiency increased two times compared with PLA nanofiber. The nanofiber mats exhibited an initial fast release during the first 3 h. Endothelial cells were cultured on nanofiber mats to investigate whether this material was toxic or not. The mats showed good biocompatibility with HUVEC. Thus, it was confirmed that nanofiber mats would not be toxic when releasing drugs during in vivo use. We think that PMPC facilitates the pass of drugs through the lipid-rich biological membrane and so anticancer drugs can be delivered to direct tumor sites. (C) 2022 Elsevier Ltd. All rights reserved.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Fizik Bilimleri; Metals and Alloys; Materials Chemistry; General Materials Science; Physical Sciences; Drug release; Electrospinning; Paclitaxel; UV-Grafting; Cancer treatment; ACCELERATED BLOOD CLEARANCE; PEGYLATED LIPOSOMES; CELL-ADHESION; PACLITAXEL; RELEASE; NANOPARTICLES; COPOLYMER; PROLIFERATION; DOXORUBICIN